Isorhynchophylline alleviates cartilage degeneration in osteoarthritis by activating autophagy of chondrocytes - Jieyun Jiang; Jin Li; Chenwei Xiong; Xindie Zhou; Ting Liu (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Context Osteoarthritis is a common degenerative disease, the cause of it is still unknown, and the treatment mainly focuses on improving symptoms. Studies have found that Isorhynchophylline (Isorhy) has antioxidant, anti-inflammatory, antiproliferative and neuroprotective effects. Objective This study investigates the role and mechanism of Isorhy in OA. Methods The destabilized medial meniscus model was used to mimic OA. Fifteen male Sprague Dawley rats were partitioned into three portions: Normal group, OA group (surgery; normal saline treatment) and OA + Isorhy group (surgery; 50 μM Isorhy treatment) were performed on the first day of every week from the 5th to the 8th week after surgery. After 4 weeks of drug treatment, the rats have been processed without debridement of the knee specimens and fixed using 4% paraformaldehyde for two days. The morphological analysis was performed by H&E, Safranin O-Fast green staining and micro-CT analysis. The specimens were researched employing Micro-CT. In the part of the aggregate methods that were evaluated by qRT-PCR and western blot of the following proteins LC3II/LC3I, Beclin-1, ATG5, ATG7, MMP3 andMMP13. Akt/PI3K signaling related proteins (p-AKT, AKT, p-PI3K, PI3K, p-mTOR, mTOR) were detected by Western blot. BECLIN1 and MMP3 were detected by Immunofluorescence assay. Results In this present research, it was proved that autophagy-related and cartilage matrix-related proteins in osteoarthritis could be regulated by Isorhynchophylline treatment. The transcriptome sequencing results suggested the regulation was closely associated with PI3K/AKT/mTOR pathway, thereby alleviating osteoarticular inflammation. In-depth study showed that Isorhy could also affect OA in rat OA models, that was indicated by H&E, Safranin O-Fast green staining, and also micro-CT analysis. Conclusion Our findings indicated that Isorhy could be regarded as a prospective candidate for OA treatment.